EKSTRAK RIMPANG KUNYIT (Curcuma longa Linn) MENURUNKAN PENYAKIT PERLEMAKAN HATI NON-ALKOHOLIK - Karmila Kaban; sunarti sunarti (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2019)
The use of recycled frying oil or deep frying oil (DFO) lead to increase in free fatty acid, trans fatty acid and free radical compound. It can cause non-alcoholic fatty liver disease (NAFLD). a chronic liver disease cause the risk for cirrhosis and heart cancer. However, there is no medicine for preventing the disease. The present study was conducted to investigate the turmeric reduces steatosis hepatocyte of male Wistar rat NAFLD model. The study used experimental randomize post-test only control group design. The 24 samples consist of four treatment groups. Group I (control): normal diet + DFO (10 μl/g/day on 6 times heating), Group II, III and IV: normal diet + DFO (10 μl/g/day on 6 times heating)+ turmeric Extract (100, 200, and 400 mg/kg/day) by given for 30 days through oral induction. The results of Kruskal-Wallis test showed a significant difference between the four treatment groups (P= 0.019) .The results of Mann-Whitney test showed significant difference in steatosis hepatocyte between the control group (P1) and treatment group(P3) the dose of 200 mg/kg BW. This suggests that a dose of 200 mg/kg BW is an effective dose in decreasing hepatocyte steatosis.